The impact of job satisfaction towards employee performance - Azmi, Zuraini (2011)
Employee attitudes are important to management because they determine the behavior of workers in the organization. The commonly held opinion is that "A satisfied worker is a productive worker". A satisfied work force will create a pleasant atmosphere within the organization to perform well. Hence job satisfaction has become a major topic for research studies. The specific problem addressed in this study is to examine the impact of job satisfaction performance. lt considered influence of age, sex and experience of employees on level of job satisfaction. Data were collected through a field survey using a questionnaire from employee in more than thirty private sector. The analysis data revealed that there exists positive correlation between job satisfaction and performance of employees